2014
DOI: 10.1016/j.bmc.2014.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of synthesized 1,4-naphthoquinone analogues on selected human cancer cell lines

Abstract: In an effort to establish new candidates with enhanced anticancer activity of 5-hydroxy-7-methyl-1,4-naphthoquinone scaffold (7-methyljuglone) previously isolated from the root extract of Euclea natalensis, a series of 7-methyljuglone derivatives have been synthesized and assessed for cytotoxicity on selected human cancer lines. These compounds were screened in vitro for anticancer activity on MCF-7, HeLa, SNO and DU145 human cancer cell lines by MTT assay. Most of them exhibited significant toxicity on cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 31 publications
1
14
0
1
Order By: Relevance
“…Extracts from Euclea natalensis possess a wide spectrum of pharmacological properties, including antibacterial [ 25 , 35 , 40 , 50 , 52 , 61 , 62 , 63 ], antimycobacterial [ 17 , 39 , 52 , 54 , 55 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ], antifungal [ 51 , 57 ], antiviral [ 18 , 71 ], antidiabetic [ 72 ], antioxidant [ 67 , 72 ], antiplasmodial [ 73 ], larvicidal [ 74 ], antischistosomal [ 75 ], molluscicidal [ 76 ], dentin permeability [ 77 , 78 ], hepatoprotective [ 79 ], cytotoxicity [ 17 , 18 , 35 , 67 , 80 ] and toxicity [ 19 ] activities as outlined below. Some of the documented pharmacological properties of crude extracts and compounds isolated from the species may be responsible for the ethnomedicinal uses of the species indicated in Table 1 .…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracts from Euclea natalensis possess a wide spectrum of pharmacological properties, including antibacterial [ 25 , 35 , 40 , 50 , 52 , 61 , 62 , 63 ], antimycobacterial [ 17 , 39 , 52 , 54 , 55 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ], antifungal [ 51 , 57 ], antiviral [ 18 , 71 ], antidiabetic [ 72 ], antioxidant [ 67 , 72 ], antiplasmodial [ 73 ], larvicidal [ 74 ], antischistosomal [ 75 ], molluscicidal [ 76 ], dentin permeability [ 77 , 78 ], hepatoprotective [ 79 ], cytotoxicity [ 17 , 18 , 35 , 67 , 80 ] and toxicity [ 19 ] activities as outlined below. Some of the documented pharmacological properties of crude extracts and compounds isolated from the species may be responsible for the ethnomedicinal uses of the species indicated in Table 1 .…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…Cytotoxicity results for the Vero cell line showed that the compound 7-methyljuglone 12 and synthesized compounds had EC 50 values ranging from 2.5 µg/mL to 36.1 µg/mL [ 71 ]. Kishore et al [ 80 ] evaluated cytotoxicity activities of 7-methyljuglone 12 isolated from the root extract of E. natalensis and a series of its derivatives on MCF-7, HeLa, SNO and DU145 human cancer cell lines using the XTT method. Most of the 7-methyljuglone derivatives exhibited significant toxicity on HeLa and DU145 cell lines with IC 50 values ranging from 5.3 µM to 10.1 µM [ 80 ].…”
Section: Pharmacological Propertiesmentioning
confidence: 99%
“…1), including antibacterial, antitrypanosome, antiviral, antiparasitic, antiplasmodial, antiinflammatory, antiproliferative and antimalarial. [1][2][3][4][5] As proved by our group 6) and Ahn's team, 7) 6-substituted 5,8-dimethoxy-1,4-naphthoquinone (DMNQ) derivatives display a higher inhibitory efficiency on DNA topoisomerase-I and the cytotoxicity against cancer cells compared with the corresponding 2-substituted derivatives due to less steric hindrance on the naphthalene ring. 8) The main mechanisms of naphthoquinones acting inhibitory activity are ascribed to the generation of reactive oxygen species (ROS) and bioreductive alkylation.…”
mentioning
confidence: 94%
“…It contains two ketone groups as crucial moieties, which are responsible for many biological activities because of their abilities to accept electrons (Benites et al, 2010[ 2 ]; O'Brien, 1991[ 32 ]). Various biological activities of 1,4-naphthoquinone derivatives have been reported, i.e., anticancer (Kishore et al, 2014[ 20 ]; Mallavadhani et al, 2014[ 26 ]; Nasiri et al, 2013[ 31 ]; Prachayasittikul et al, 2014[ 35 ]; Sreelatha et al, 2014[ 42 ]), radical scavenging (Kumar et al, 2013[ 21 ]; Lebedev et al, 2008[ 24 ]; Song et al, 2000[ 40 ]), antimicrobial (Ryu and Kim, 1992[ 37 ]; Sreelatha et al, 2014[ 42 ]; Tandon et al, 2009[ 45 ]), antiviral (Crosby et al, 2011[ 9 ]; Da Costa et al, 2013[ 10 ]; Ilina et al, 2002[ 16 ]), antifungal (Castro et al, 2013[ 6 ]; Pawar et al, 2014[ 33 ]; Tandon et al, 2009[ 45 ]), antitrypanocidal (Salmon-Chemin et al, 2001[ 38 ]) and antiplatelet (Jin et al, 2004[ 17 ]; Kuo et al, 2011[ 22 ]; Lien et al, 2002[ 25 ]; Yuk et al, 2000[ 48 ]) activities. It was found that structural modification can effectively modulate the electrochemical behavior of 1,4-naphthoquinone compounds, thereby affecting their biological activities (Hillard et al, 2008[ 15 ]).…”
Section: Introductionmentioning
confidence: 99%